Factors affecting the demand for native chicken eggs in Surakarta City. Issue 1 (November 2021) - Setyawati, A K; Marwanti, S; Sundari, M T
Abstract: Native chicken egg is one of the animal protein sources to meet the need for protein. This study analyzes what factors affect the demand for native chicken eggs in Surakarta City and examine the elasticity of demand for native chicken eggs in Surakarta City. The primary method of research is descriptive. This research was conducted in Harjodaksino Market, Jongke Market, Legi Market, Gede Market, dan Sangkrah Market. This study carried out the research location selection purposively and used 100 respondent end consumers of native chicken eggs. The data analysis method used is multiple linear regression. The result showed that factors that affect the demand for native chicken eggs in Surakarta City are native chicken eggs prices, laying hen eggs prices, duck egg prices, native chicken meat prices, broiler chicken meat prices, and rice prices. Price elasticity indicates that the demand for native chicken eggs is elastic. Cross elasticity showed that laying hen eggs, duck eggs, and native chicken meat are substitute goods for native chicken eggs. In contrast, broiler chicken meat dan rice is complementary good for native chicken eggs.